The real-world safety profile of pemetrexed and platinum with or without pembrolizumab: insights from a comparative analysis of FAERS database - Shun Li; Zhifei Huang; Xiaoyu Zhong; Yan Zhou; Hao Jiang (BMC Cancer, 2025)
Abstract Background Lung cancer (LC) is a leading cause of cancer-related mortality worldwide. The combination of immune checkpoint inhibitors (ICIs) with chemotherapy significantly extends survival but increases the risk of treatment-related toxicity. To explore the impact of adding pembrolizumab to pemetrexed and platinum on treatment-related toxicity, this study utilized the FDA Adverse Event Reporting System (FAERS) to assess the safety of pemetrexed and platinum with or without pembrolizumab in LC patients. Methods We collected data from FAERS database between the second quarter of 2017 and the third quarter of 2024. Disproportionality analysis was conducted using the Reporting Odds Ratio (ROR), Proportional Reporting Ratio (PRR), Bayesian Confidence Propagation Neural Network (BCPNN), and Multi-Item Gamma Poisson Shrinker (MGPS). Additionally, comparative analysis was performed using the ROR method. Results Among LC patients receiving chemotherapy alone (pemetrexed + platinum) and combination therapy (pembrolizumab + pemetrexed + platinum), adverse event (AE) reports were 2871 and 5443 cases, respectively. Compared to chemotherapy alone, combination therapy was associated with a higher risk of renal and urinary disorders, hepatobiliary disorders, and interstitial lung disease (ILD), pneumonitis and other AEs. Subgroup analysis revealed that gender and age may be influential factors in the occurrence of AEs. Combination therapy prolonged the time to onset of AEs. Conclusions In the real world, combination therapy increases the risk of certain AEs, particularly in specific patient subgroups. These findings emphasize the importance of personalized treatment strategies and AE monitoring, particularly during the first three months of therapy.